Adults of the cerambycid beetle Megacyllene caryae use both olfactory and visual information to locate mates. Issue 5 (3rd April 2019) - Johnson, Todd D.; Hanson, Elizabeth; Yu, Allen
Abstract: Many species of beetles in the family Cerambycidae use volatile pheromones to facilitate the location of mates. Visual cues may also influence the location of mates, as the adults of many species of cerambycids are often brightly patterned and diurnal. Theory predicts that combining signals or cues of different modalities (e.g., chemical, visual) to transmit information will increase the likelihood of an organism responding to this information, compared to when the signal or cue is presented alone. Here, we test the hypothesis that attraction of adults of the cerambycid beetle Megacyllene caryae (Gahan) (Coleoptera: Cerambycidae, Clytini) to their pheromones will be increased when visual cues are present. Consistent with that hypothesis, the number of beetles caught by traps baited with pheromones was increased 3.4‐fold when a dead adult beetle of that species was attached to the trap, relative to those with just pheromone alone. Capture of M. caryae in our study was also influenced by the position of traps within forest stands, with traps at 100 m within stands catching 2.5× as many beetles as traps at the forest edge. These findings suggest that vision and visual cues play an important role in the location of mates by cerambycid beetles and warrant further research. Also, the inclusion of visual cues on traps may enhance the efficacy of trapping cerambycid beetles, such as the detection of species that are non‐native and potentially invasive, or when monitoring species that are native and of conservation concern. Abstract : We demonstrate the importance of visual cues for mate‐location by Megacyllene caryae (Coleoptera: Cerambycidae) in the field. Including a visual cue with a known pheromone of the beetle increased capture of adults by 3.4‐fold compared to the pheromone alone. This indicates that visual cues are important to the behavioral sequence of mate‐location by M. caryae : the pheromone is the primary attractant that brings conspecifics to the proximity of the emitter, whereas visual cues assist in mate‐location at short ranges.